2018
DOI: 10.1111/odi.12998
|View full text |Cite
|
Sign up to set email alerts
|

Orthognathic surgery induces genomewide changes longitudinally in DNA methylation in saliva

Abstract: Objective Orthognathic surgery dramatically changes morphology of the maxillofacial deformity and improves the malocclusion morphologically and functionally. We investigated the influence of orthognathic surgery on genomewide DNA methylation in saliva. Methods Saliva was obtained from nine patients undergoing orthognathic surgery and two healthy reference individuals before and 3 months after orthognathic surgery. Genomewide DNA methylation profiling of saliva (341,482 CpG dinucleotides) was conducted using In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…It was perhaps due to the response to surgical stress or bone injury. 41 In neurodegenerative diseases, Chuang et al unveiled five significant CpGs. 42 Elaheh et al observed allele-specific methylation in CD4 + cells instead of saliva.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was perhaps due to the response to surgical stress or bone injury. 41 In neurodegenerative diseases, Chuang et al unveiled five significant CpGs. 42 Elaheh et al observed allele-specific methylation in CD4 + cells instead of saliva.…”
Section: Dna Methylationmentioning
confidence: 99%
“…MALDI-TOF mass spectrometer 27 CpG sites in the promoter (MT2 region) 25 2. Infinium HumanMethylation450K array 485 000 probes 26 , 35 , 37 , 41 , 42 , 44 , 46 , 47 , 51 , 301 3. ddPCR (1) cg05575921 and DMR16( 27 , 29 , 30 2) cg14361627, cg14361627, cg08928145 and cg07547549 302 4. Illumina MethylationEPIC BeadChip 795,694 probes 33 , 54 5. methylation specific polymerase chain reaction and agarose gel electrophoresis (1) p16INK4a and p14ARF 28 (2) SOCS1 40 (3) p16, DAP- K, MGMT, and GSTP1 38 (4) ZNF282 and HPCAL1 52 6. targeted bisulfite sequencing (TBS) protocol 3.1 million CpG sites 34 7. pyrosequencing (1) LEP, ICAM-1, CRH, and LINE-1 genes 36 (2) BDNF 45 (3) NMUR2 and UBE2U 50 (4) ZC3H12D, BCAS4 and cg06379435 53 (5) FADS1 and FADS2 43 8. real-time methylation-specific polymerase chain reaction (1) P16 39 …”
Section: Introductionmentioning
confidence: 99%